Sensory and motor effects of dexmedetomidine as an adjuvant to bupivacaine for brachial plexus block - Yousry Kandil (Wolters Kluwer Medknow Publications, 2018)
Background Dexmedetomidine is a highly selective (eight time more selective than clonidine), specific, and potent α2-adrenergic agonist having analgesic, sedative, antihypertensive, and anesthetic sparing effects when used in systemic routes. Patients and methods Forty patients of both sexes, aged between 25 and 70 years; American Society of Anesthesiologists I-II, who were submitted to elective upper limb surgery by supraclavicular brachial plexus block were included in the present study. They were selected during the period from March 2016 to June 2017. The patients were divided randomly by sealed envelopes into two equal groups (n=20). Group I: 20 patients received 30 ml bupivacaine 0.25%. Group II: 20 patients received 30 ml bupivacaine 0.25% plus 100 μg dexmedetomidine. Results The duration was reported in group II 13.13±1.10 and 16.50±1.63 min for the onset of sensory and motor blocks, respectively, and in group I 14.90±1.18 and 18.63±1.12 min for the onset of sensory and motor blocks, respectively. There was significant decrease of median pain score in group II when compared with group I at 4, 8, 12, 16, 20, and 24 h postoperatively. Conclusion Dexmedetomidine had significantly better postoperative analgesic effects, longer duration of sensory and motor blockade, and earlier onset of action. However, it had unwanted side effects in the form of transient bradycardia and hypotension.